Short-term effects of high-concentration uranium pollution on soil enzyme activity and microbial metabolism in farmland soil - HUANG Sen; CHEN Xiaoming; ZHANG Guyu; HUANG Jiali; ZHANG Lili; XU Yuxuan (Fushe yanjiu yu fushe gongyi xuebao, 2022)
To explore the short-term impact of uranium pollution on the microecology of farmland soil, this study investigated the activities of four enzymes involved in key soil processes (β-glucosidase, urease, phosphatase, and arylsulfatase) and analyzed the changes in microbial metabolic activity, carbon utilization capacity, and diversity using Biolog EcoPlate under short-term (3 d, 13 d, and 20 d) uranium treatments (0 mg/kg, 50 mg/kg, 200 mg/kg, and 500 mg/kg). The results showed that the activities of the three soil enzymes, except that of urease, were inhibited by uranium pollution, especially phosphatase activity, which was reduced by 75.9% in the 20-day U500 treatment group. In addition, microbial metabolic activity was inhibited by uranium pollution. However, the inhibition effect showed a downward trend with the extension of the treatment time. The carbon metabolism capacity of microorganisms was inhibited. By contrast, the ability of microorganisms to utilize amino acids, carbohydrates, and polymer carbon sources was positively correlated with time in the U50 treatment group. The results of diversity indices analysis and sho principal component analysis wed little effect on the microbial diversity of uranium contamination. Therefore, uranium pollution inhibited the metabolic activities of farmland soil microorganisms, especially the carbon, phosphorus, and sulfur cycles. This study provides a direction for the ecological restoration of farmland soil uranium pollution.